KAJIAN FOLKLORE: MAKNA DAN SIMBOL PRABU SILIWANGI BERTAPA DAN MENYUCIKAN DIRI SEBELUM MASUK ISLAM DI MATA AIR CITARUM - Nurcahya, Yan; Supendi, Usman (Historia Islamica: Journal of Islamic History and Civilization, 2025)
Abstract: Folklore is a discipline, which stands alone in Indonesia, which has not been developed for long. Folklore is part of a collective culture, which is spread and passed down from generation to generation. To be able to distinguish it from culture. History is an empirical science. The consequence is that every historical statement must be based on a reliable source (fact). There is no historical source, no historical source then there is no history. This is what distinguishes history from fairy tales. Storytelling is a product of fictional imagination. In fairy tales, there is no claim that the story is told based on empirical facts or not, whether it really happened or not. Through Patilasan Dipatiukur and Prabu Siliwangi we can reflect on the struggle and courage that shaped the history of this nation. The traces of Dipatiukur and Prabu Siliwangi carved in every stone and puddle of water in this place remind us of the importance of respecting and studying valuable historical heritage.Keywords: Pajajaran Kingdom, Spread of Religion, Islam, Sundanese History Abstrak:Folklor merupakan suatu disiplin, yang berdiri sendiri di Indonesia, yang belum lama dikembangkan. Folklore merupakan sebagian kebudayaan suatu kolektif, yang tersebar dan diwariskan turun temurun. Untuk dapat membedakan dengan kebudayaan. Sejarah merupakan ilmu empiris. Konsekuensinya adalah setiap pernyataan sejarah harus didasarkan pada sumber (fakta) yang dapat diandalkan. Tidak ada sumber sejarah, tidak ada sumber sejarah maka tidak ada sejarah. Inilah yang membedakan sejarah dari dongeng. Bercerita merupakan produk imajinasi fiktif. Dalam dongeng, tidak ada klaim bahwa cerita tersebut diceritakan berdasarkan fakta empiris atau tidak, benar-benar suatu kejadian atau tidak. Melalui Patilasan Dipatiukur dan Prabu Siliwangi kita dapat merenungi perjuangan dan keberanian yang membentuk sejarah bangsa ini. Jejak Dipatiukur dan Prabu Siliwangi yang terukir dalam setiap batu dan genangan air di tempat ini mengingatkan kita akan pentingnya menghormati dan mempelajari warisan sejarah yang berharga Keywords: Kerajaan Pajajaran, Penyebaran Agama, Sejarah Sunda, Folklor